2012
DOI: 10.1095/biolreprod.111.098079
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 31 (GJB3) Deficiency in Mouse Trophoblast Stem Cells Alters Giant Cell Differentiation and Leads to Loss of Oxygen Sensing1

Abstract: The nonphysiological placental oxidative environment has been implicated in many complications during human pregnancy. Oxygen tension can influence a broad spectrum of molecular changes leading to alterations in trophoblast cell lineage development. In this study, we report that mouse wild-type trophoblast stem cells (TSCs) react to low oxygen (3%) with an enhanced differentiation into the giant cell pathway, indicated by a downregulation of the early stem cell markers Eomes and Cdx2 as well as by a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The major finding of our study is that Cx31.1 has a directly opposed function to Cx31 on TSC differentiation and placental development. Cx31 deficiency enhances TSC differentiation into placental subpopulations [10,12,13], whereas the absence of Cx31.1 delays this process. Thus, both connexins are rather collectively balancing TSC fate by having opposite regulatory effects on differentiation processes than serving the same molecular functions by just having redundant properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major finding of our study is that Cx31.1 has a directly opposed function to Cx31 on TSC differentiation and placental development. Cx31 deficiency enhances TSC differentiation into placental subpopulations [10,12,13], whereas the absence of Cx31.1 delays this process. Thus, both connexins are rather collectively balancing TSC fate by having opposite regulatory effects on differentiation processes than serving the same molecular functions by just having redundant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Upon differentiation, Cx31-deficient TSC show an earlier temporal induction of the Ascl2 (Mash2) gene and subsequently the SPT marker gene Tpbpa, the syncytiotrophoblast marker Cx26 (Gjb2), and the TGC marker Prl3d1 (Pl-1, placental lactogen 1), compared to wild-type controls, which indicates an endogenous, enhanced differentiation of TSC [12]. A recent study analyzing markers for the different TGC populations, showed that Cx31-deficient TSC, in particular, reveal an upregulation of secondary TGC markers Prl2c2/Plf, Prl3b1/Pl-2, and Ctsq [13].…”
Section: Introductionmentioning
confidence: 99%
“…After 24 h of serum starvation, the cells were treated with 1 mg/ml g-rhCCN1, g-rhCCN3, or PBS/0.1% BSA as a solvent control for 24 h. Annexin V apoptosis assays were performed as described by Koch et al 25 using flow cytometry (FACSCalibur, Becton Dickinson) in combination with FITC-coupled annexin and propidium iodide (PI; BD Pharmingen).…”
Section: Annexin V Apoptosis Assaymentioning
confidence: 99%
“…In the mature mouse placenta, the subtypes of TGCs on the venous side, Ch-TGCs and P-TGCs, are exposed to deoxygenated blood whereas SpATGCs and C-TGCs are in contact with oxygenated blood, and STGCs are bathed in diminishing concentrations of oxygen depending on the level within the labyrinth. Previous studies with trophoblast stem (TS) cells grown as adherent monolayers, showed that culturing in 3% oxygen, compared to the atmospheric levels ( $ 20%), increased expression of a P-TGC-specific gene (Prl3d1/Pl1α) but had no effect on other TGC-specific genes (Koch et al, 2012). The cellular response to low oxygen levels is regulated by a family of transcription factors, known as hypoxia inducible factors (Hifs).…”
Section: Introductionmentioning
confidence: 99%